Dynamic characteristics and stability criterion of rotary galloping gait with an articulated passive spine joint. (16th February 2017) - Wang, Chunlei; Zhang, Ting; Wei, Xiaohui; Long, Yongjun; Wang, Shigang
Abstract: Based on the simplified planar quadruped model with a passive spine joint, this paper focuses on studying the effect of the spine joint on the dynamic performance and the stability of the rotary galloping gait. The stable, periodic, and symmetric rotary galloping gait is achieved by the particle swarm optimization method without any parameter symmetry for leg motion and without any limitation for spine motion. By analyzing the symmetric pattern of the rotary galloping gait, the stability criterion is derived: the closer to zero is the pitching angle at peak time of the center of mass, the better is the stability of the galloping gait. Then, we study the effect of rear leg touchdown angle and spine stiffness on the stability. Moreover, the unstable rotary galloping gait can be stabilized by adjusting one or more of the touchdown angle, spine stiffness, and leg stiffness. Furthermore, the effect of the spine stiffness on the key kinematic and kinetic properties is also studied for different initial values and mechanical parameters. The presented stability criterion and the achieved dynamic performance analysis results will be instructive for the design and control of the quadruped robot. Abstract :